Effets du type et de la position de l'explant sur l'induction de cals chez le gerbera (Gerbera jamesonii Bolus) - Haouala, F.; Farhat, N.; Chabchoub, L. (Tropicultura, 2010)
Effects of Explant Kind and Position on Calli Induction in Gerbera (Gerbera jamesonii Bolus). Callogenesis in gerbera (Gerbera jamesonii Bolus 'Fredigor') was successfully induced from leaves and floral peduncles on a medium containing 1 mg.l-1 2.4-D and 1 mg.l-1 BA. Explant source and position had clear effects on callogenesis rate. This was higher for leaf explants and apical positions. Calli growth was good for the two kinds of explants. Calli were compact, nodulous and creamy only on media containing auxin (2.,4-D) and cytokinin (BA or kinetin). Fresh weight of calli depends of callogenesis medium, explants source and position.